Structure Based Virtual Screening of Rivastigmine Derivatives as Cholinesterase Inhibitors (International Journal of Pharmaceutical Sciences and Drug Research, 2023)
The interaction of large protein molecules with small drug molecules is studiedthrough in silico studies. The molecular docking and other important pharmacokinetic (ADMET) propertiesof the compounds were carried out withrivastigmine and its derivatives againstprotein Bovine Serum Albumin (PDB: 4F5S) to describe their better protein-ligand interactions and binding affinities. Rivastigmineisapromising drug that is usedto treat Alzheimerdisease.But due to the increased drug resistance property, its use becomes less effective.Hence, better drugs with higher potency are needed against this Alzheimer disease. In order to design a more potent drug computationally, we have taken here 52 derivatives of Rivastigmineand were docked against protein Bovine Serum Albumin. Besides, quantum chemical parameters like HOMO-LUMO bandgap energy and other important pharmacological analysis like ADMET studies were also carried outto predictbetter drug candidature. Molecular dynamics simulation and MMPBSA binding free energy calculations were also validated. From this computational study, 14 designed compounds werefound to have better potencyagainst Alzheimer disease.